UPAYA MASYARAKAT MELAYU KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI DALAM MENCEGAH DAN MEMBERANTAS PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOTIKA DAN PREKURSOR NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Hidayat, Andri; Erdianto, Erdianto; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Narcotics based on article 1 paragraph (1) of Law Number 35 of 2009concerning Narcotics which reads "narcotics are substances or drugs derivedfrom plants, both synthetic and semisynthetic, which can cause a decrease orchange in consciousness, loss of taste, reduce to eliminate taste. pain, and canlead to dependence, which are differentiated into groups as attached in this Law". Narcotics precursors are substances or starting materials or chemicals that canbe used in the manufacture of narcotics which are differentiated in the table asattached to this Law.This type of research can be classified into sociological juridicalresearch where the research tests the effectiveness of the current law. Thissociological research is a type that is viewed from the purpose of legal research.Sociological or empirical legal research consists of legal identification(unwritten) and research on the effectiveness of the law.The research objectives of this thesis are; First, public participation isseen from Article 104 of Law Number 35 Year 2009 concerning narcotics, whichstates that “the public has the widest opportunity to participate in helping toprevent and eradicate the abuse and illicit trafficking of narcotics and narcoticprecursors. The two efforts made by the Malay community of Pangean District inpreventing the circulation and abuse of narcotics.From the research results, based on two problem formulations it can beconcluded. First, so far the community has not fully participated in the preventionand trafficking of narcotics and narcotics precursors, it can be seen from theincreasing number of use and circulation of narcotics in Pangean sub-district.Second, preventive efforts have been made to the maximum extent possible by thevillage apparatus working together with the Police to disseminate information onthe dangers of narcotics abuse and narcotic precursors. However, the problem isin the form of implementation or real action from the community.Keywords: Narcotics, Community Efforts, Prevention